Reasonable width and control technology of narrow coal pillar in gob-side entry driving in deep-buried bump-prone coal seam - TANG Dongxu; ZHAO Wenguang; ZHANG Junwen; BAN Dingcheng (矿业科学学报)
Aiming at the problem of large deformation of surrounding rock and difficulty of control gob-side entry driving in deep coal seam, taking the setting of narrow coal pillar in gob-side entry driving in deep-buried bump-prone coal seam as the engineering background, the reasonable range of narrow coal pillar width is calculated by combining theoretical analysis, numerical simulation and field test based on the limit equilibrium theory. The distribution and evolution of vertical stress and elastic energy density in narrow coal pillar and solid coal are analyzed by constructing numerical models of different narrow coal pillar widths and roadway driving widths. The results show that when the minimum width with narrow coal pillar is 5.04m and the width of roadway is 5.4m and 6.0m, the maximum width of coal pillar is 6.8m and 6.2m, respectively. The narrow coal pillar with reduced width still has a good bearing capacity and is subjected to low stress and low energy level, can effectively avoid large deformation of roadway and reduce the bump risk.